‘Little Ice Age’ precipitation in Jotunheimen, southern Norway - Rasmussen, L.A.; Andreassen, L.M.; Baumann, S.; Conway, H. (The Holocene, 2010)
Recently published glaciological data from southern Norway enable analysis of changes in glacier geometry since the ‘Little Ice Age’ (LIA) and estimation of the magnitude of the LIA precipitation anomaly. Glacier area extents in the Jotunheimen region have been created for 2003 using glacier outlines derived from Landsat, and for the LIA maximum (about AD 1750) by using glacier outlines defined by moraines. A 25 m digital terrain model from 1980 was used to derive inventory data for both times. Both inventories provide area and altitude range, as well as length, slope and aspect of the glaciers. Area-altitude profiles A(Z) for the LIA maximum are calculated from the 1980 profiles by assuming that the area-increase distribution Δ A(Z) was concentrated at low altitude and it integrates to the measured area difference between 1980 and the LIA. Under this assumption, the regionally averaged mean altitude change from 1980 to the LIA, Δ Z = 68 m. Glacier mass balance measurements show that the mass balance gradient varied little from year to year over recent decades. Further, mass balance profiles b(z) are nearly linear, so the average balance B over the area—altitude profile is equal to the balance at the mean altitude b(Z) When the observed balance gradient is applied to the mean Δ Z it yields a mass balance anomaly Δ B = +0.60 m w.e./yr, which includes an adjustment of +0.20 m w.e./yr to account for the fact that in 1980 the glaciers were not in equilibrium with the climate. Published data indicate that mass balance sensitivities are 0.14 m w.e./yr per 10% increase in precipitation and −0.55 m/yr w.e. per °C warming, and that temperature in the region was about 0.5°C lower than present during the LIA; using these constraints, we calculate a LIA precipitation anomaly relative to 1961—1990 Δ P of +24±22%.